Grupo Gruta de Teatro: memórias e militâncias no teatro paraense (1967-1981) - SOUSA, Bento Henrique Oliveira de (2021)
This course conclusion paper aims to record chronologically the history of the Grotto Theater Group and aims to produce an analysis of its artistic trajectory and its contributions to the history of theater produced in the State of Pará. Oral that seeks through oral sources the production of documents, as well as studies of Memory, triggering authors who produce on the subject such as: Ferreira (2006); Bosi (2003); Freitas (2006) among others, and assisting with the Historiography of the Theater in Pará I call Bezerra (2013); Salles (1994) and Jansen (2009) these authors have valuable contributions to the historiography of Pará theater. The Grotto is one of the oldest theater groups still active in the state of Pará. The Grotto is a school and continues to produce theater.